The Role of Sustainable Agriculture in Supporting Economic Development and Food Security: A Literature Review 2019–2024 - Ummul Hikmah Saragih; Tantio Ovalti (Journal of Economics, Management, Development, and Education, 2026)
This study examines the role of sustainable agriculture in supporting economic development and food security through a literature review of scientific journals published between 2019 and 2024. This study stems from the issues of increasing food demand, the economic vulnerability of rural communities, and environmental pressures on agricultural systems. This study aims to synthesize empirical and conceptual findings related to the contribution of sustainable agriculture to economic growth and strengthening food security. The method used is a systematic literature study by analyzing relevant scientific articles using content and thematic analysis approaches. The results of the study show that sustainable agriculture plays an important role in increasing agricultural productivity, strengthening farmers' incomes, creating economic added value, and improving food system security. Sustainable agricultural practices also contribute to food availability, access, quality, and stability through efficient and adaptive resource management. These findings confirm that the integration of sustainable agriculture into development policies can promote inclusive economic development while strengthening food security in the long term.